Mechanical and Microstructural Analysis of Treated Tuff with Metakaolin Geopolymer Cement for Road Base layers Applications - Khadhra Allali; Nabil Bella (The Journal of Engineering and Exact Sciences)
Traditional road bases materials such as natural gravel and crushed stone are environmentally damaging, and there is a growing need for sustainable and eco-friendly alternatives. One such alternative is using geopolymer cement and tuff as aggregate materials. Geopolymer cement is an innovative and environmentally-friendly alternative to traditional Portland cement, and using locally-sourced tuff as an aggregate material can further reduce the environmental impact of road construction. This article discusses the importance of sustainable road construction practices, particularly in the use of eco-friendly materials for road base layers. It focuses on the treatment of tuff with alkali-activated metakaolin as the geopolymer precursor activated with a mixture of sodium hydroxide and sodium silicate. The effectiveness of treating tuff with metakaolin geopolymer cement is evaluated using several parameters, including dry density, California Bearing Ratio (CBR), shear strength, and microstructure analysis. These evaluations are performed with different NaOH dosages (8, 10, and 12  moles) to determine the optimal molarity for enhancing the material's performance.